2009
DOI: 10.4103/0972-124x.60229
|View full text |Cite
|
Sign up to set email alerts
|

Piezosurgery in periodontology and oral implantology

Abstract: Periodontitis is a chronic inflammatory disease of the tooth-supporting structures. The treatment of this condition is largely based on the removal of local factors and restoration of the bony architecture. Moreover, in the era of modern dentistry, successful implant therapy often requires sound osseous support. Traditionally, osseous surgery has been performed by either manual or motor-driven instruments. However, both these methods have their own advantages and disadvantages. Recently, a novel surgical appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…The risk of sinus-membrane perforation is low with 6% compared to lateral approach sinus-lift procedures performed with rotating instruments with a reported perforation rate of 14% -56% [42] due to the use of diamond coated ultrasonic instruments which are known to be highly safe on soft tissues [43][44][45][46]. Since all surgeons -backed by experimental results published [41]-decided to proceed with subantral grafting even in these reported cases of sinus-membrane-perforation, only 2 implants (0.31%) were lost in these cases, suggesting a perforation as described by Jank et al [41] not to be a reason to interrupt the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of sinus-membrane perforation is low with 6% compared to lateral approach sinus-lift procedures performed with rotating instruments with a reported perforation rate of 14% -56% [42] due to the use of diamond coated ultrasonic instruments which are known to be highly safe on soft tissues [43][44][45][46]. Since all surgeons -backed by experimental results published [41]-decided to proceed with subantral grafting even in these reported cases of sinus-membrane-perforation, only 2 implants (0.31%) were lost in these cases, suggesting a perforation as described by Jank et al [41] not to be a reason to interrupt the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Various studies[ 7 ] on Piezosurgery ® have shown rapid regeneration and reduced healing period, which was also evident in the present case, due to an antiseptic effect provided by the release of oxygen molecules and rapid metabolic rate of cells stimulated by the piezoelectric vibrations. Various other benefits of Piezosurgery ® include no risk of emphysema due to the aerosol effect that the ultrasonic device produces unlike the effect of air-water spray generated with rotary instruments, reduced postoperative pain due to less invasive nature and reduced traumatic stress to the patient due to the noise-less nature of the microvibration,[ 3 4 7 9 ] all of which were well appreciated by the patient as well as operator in the present case.…”
Section: Discussionmentioning
confidence: 74%
“…One of the advantage of using Piezosurgery ® device is lesser postoperative pain;[ 4 ] therefore, after surgery, only mild analgesic tablets of acetaminophen 500 mg, thrice daily for 5 days and an antibiotic, amoxicillin 500 mg thrice daily for 5 days were prescribed. Furthermore, rinsing with 0.12% chlorhexidine gluconate mouthwash (Rexidine® Indoco Remedies Ltd.) twice daily for a period of 1 month was prescribed.…”
Section: Case Reportmentioning
confidence: 99%
“…Piezosurgery is an advantageous technique for delicate structures in the oral and maxillofacial region, respect to osteotomies of thin and fragile bones the application of ultrasound is superior to other mechanical instruments because of the extremely precise and virtually arbitrary cut geometries, easy handling, efficient bone ablation and minimal accidental damage to adjacent soft tissue structures ( 7 ). It is helpful to perform bone cutting with great precision facilitating ridge augmentation and ridge expansion, tooth extraction, ankylotic tooth extraction and surgical orthodontic surgeries, while precluding injury to soft tissue, minimal heat is generated during cutting, thus maintaining vitality of adjacent tissue ( 8 ).…”
Section: Introductionmentioning
confidence: 99%